Model Aplikasi Pengelolaan Administrasi Usaha Guest House - Rahman Hidayat; Ruliah Ruliah (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2015)
In the fierce competition with efforts to keep customer inn does not move the promotional strategy was used at a discount price. In the House of Mecca using a promotional discount on the price based on the number of inpatient but in practice this price discount less running smoothly because they still use manual data collection by recording the book slows officer records lodging guests and determine the guests deserve a discount.In this article constructed Guest Applications Lodging with discount In House Mecca appropriate help and speed up the data entry process and the determination of a price discount.The test results showed that the use of User Acceptance 28.33% strongly agree, agree 47.67%, 19.33% quite agree, disagree 4.67%, and 0% strongly disagree, it can be concluded that this application is appropriate and can be help out. Keywords: Discount, Applications, Guest House.